PENGARUH NILAI INDIVIDU TERHADAP PERSEPSI INTENSITAS MORAL (Studi Empiris Mahasiswa Akuntansi UNIMMA) - Ekhananto, Dian; Suprianto, Edy (JURNAL ILMIAH EDUNOMIKA, 2024)
Personal or individual values are fundamental beliefs that explain a person's mode of behavior or hope for a better end state so that the action becomes a personal and social preference over other modes of behavior or actions that are opposite. Values are criteria in the daily lives of individuals in social life in formulating preferences and selecting available alternative options. Individual values have an important function in making decisions. The research aims to evaluate individual values regarding the ability to explain differences in perceptions of moral intensity when moral behavior is faced with the same problem. This research using primary data used a total of 100 accounting students at the Muhammadiyah University of Magelang as respondents. The sampling method was purposive sampling of accounting students who were actively studying and had completed auditing I courses or students in semesters VII-IX. Of the 100 respondents, only 98 questionnaires were processed and the remainder were not returned. Hypothesis testing regarding the influence of individual values or norms on perceptions of moral intensity is used, namely multiple regression analysis. Multiple regression testing provides empirical evidence that there is a significant influence related to personal values (individual values, social values of society, and moral values) partially in a perception of moral intensity.